Pertanggungjawaban Pidana terhadap Pelaku Penjualan Deepfake Porn di Media Sosial X - Rachmat Sucipto, Kevin; Zairani Lisi, Ivan; Gusta Andini, Orin (Institut Agama Islam Nasional Laa Roiba Bogor, 2025)
The absence of specific legislation regulating Artificial Intelligence has resulted in the lack of a special criminal offense qualification that can serve as a legal basis for imposing criminal liability on perpetrators. This condition creates a legal dilemma when the Principle of Legality is confronted with criminal acts such as the sale of Deepfake Porn on the social media platform X, which utilizes Artificial Intelligence-based technology. This research aims to examine the relevant criminal offense qualifications applicable to such acts and determine the appropriate statutory provisions for imposing criminal liability on perpetrators. The research employs a doctrinal legal research method with a statutory approach and a conceptual approach. The findings indicate that the Cybercrime Criminal Offense Qualification is more relevant than the Pornography Criminal Offense Qualification due to the principle of lex consumen derogat legi consumte, based on the locus and characteristics of the Deepfake Porn sale. Perpetrators may be held criminally liable with a maximum imprisonment sentence of 16 years and/or a maximum fine of sixteen billion Rupiah pursuant to the criminal provisions of Article 35 in conjunction with Article 51 paragraph (1) of Law Number 11 of 2008 concerning Electronic Information and Transactions (ITE Law) as the primary provision, along with other criminal provisions from the amendments to the ITE Law (Law Number 19 of 2016 and Law Number 1 of 2024), Law Number 27 of 2022 concerning Personal Data Protection, and Law Number 44 of 2008 concerning Pornography.